Temperature dynamics during nonisothermal evaporation from drying porous surfaces. Issue 11 (14th November 2013) - Aminzadeh, M.; Or, D.
Key Points Analytical quantification of evaporation rate and surface temperature coupling Offering a physical basis for interpreting empirical remote sensing methods Quantifying the difference between isothermal and non‐isothermal evaporation